STUDENTS’ GRAMMAR MASTERY AND WRITING ABLITY: HOW IS THE CORRELATION? - Putu Ayu Trisna Devi; I Gde Putu Agus Pramerta; Ida Ayu Made Sri Widiastuti (Academic Journal on English Studies (AJOES), 2023)
In English language there are several language components and skills. There are grammar and writing that take an important role and crucial to be learned by the students because it can help students to get better results in English. Therefore, regarding the importance of grammar and writing for students, the researchers conducted this study that discussed about the correlation between grammar mastery and writing ability. This research aimed to find out the correlation between grammar mastery and writing ability. The sample was consisted of 37 students which was the eighth-grade students of SMP (SLUB) Saraswati 1 Denpasar in academic year 2022/2023. Moreover, there were two tests, namely, the completion test for grammar mastery and paragraph construction test for writing ability. SPSS 25.0 program was used to analyze the data. The result showed that there was a significant correlation among the variables: r value 0.924. It showed very high-level correlation because it was in the interval 0.80-1.000. Therefore, grammar mastery should be considered on teaching writing ability.